A single-ion conducting and shear-thinning polymer electrolyte based on ionic liquid-decorated PMMA nanoparticles for lithium-metal batteries. Issue 47 (17th November 2016) - Li, Yang; Wong, Ka Wai; Dou, Qianqian; Ng, Ka Ming
Abstract : A single-ion conducting polymer electrolyte based on ionic liquid-decorated PMMA nanoparticles exhibits excellent electrochemical performances. Abstract : A novel single-ion conducting polymer electrolyte (SIPE) based on ionic liquid (IL)-decorated PMMA nanoparticles dispersed in a propylene carbonate (PC) host is reported. This SIPE possesses a superior lithium-ion transference number ( t Li + ) of 0.96 with an enhanced ionic conductivity of 3.13 × 10 −3 S cm −1 at room temperature and a wide electrochemical window up to ∼5.18 V. The enhanced ionic conductivity is ascribed to the unique brush-like structure of ionic liquid groups tethered to PMMA nanoparticles. Furthermore, the developed SIPE was found to be more efficient in suppressing lithium dendrite formation on a cycled lithium anode. As little as 11 wt% PMMA-IL-TFSI in a LiTFSI/PC host produces more than a ten-fold increase in the cell lifetime. On the other hand, this SIPE exhibits shear-thinning behavior which can be advantageously utilized in electrolyte processing. In addition, galvanostatic cycling measurements in Li/Li4 Ti5 O12 half cells using this SIPE exhibit excellent rate performance. Even at an extremely high charging rate of 875 mA g −1 (5C), the capacity is still around 100 mA h g −1, that is over 57% of the theoretical capacity (175 mA h g −1 ). These attributes enable the developed SIPE to be a promising candidate for high-performance lithium batteries.